Custodians of the land : ecology & culture in the history of Tanzania - Maddox, Gregory; Giblin, James Leonard; Kimambo, Isaria N. (London : James Currey ; Athens : Ohio University Press, 1996)
"Farming and pastoral societies inhabit ever-changing environments. This relationship between environment and rural culture, politics and economy in Tanzania is the subject of this volume which will be valuable in reopening debates on Tanzanian history." "In his conclusion, Isaria N. Kimambo, a founding father of Tanzanian history, reflects on the efforts of successive historians to strike a balance between external causes of change and local initiative in their interpretations of Tanzanian history." "He shows that nationalist and Marxist historians of Tanzanian history, understandably preoccupied through the first quarter-century of the country's post-colonial history with the impact of imperialism and capitalism on East Africa, tended to overlook the initiatives taken by rural societies to transform themselves." "Yet there is good reason for historians to think about the causes of change and innovation in the rural communities of Tanzania, because farming and pastoral people have constantly changed as they adjusted to shifting environmental conditions."--Jacket.
Introduction : custodians of the land : ecology & culture in the history of Tanzania / James Giblin & Gregory Maddox -- pt. 1. Environmental & demographic change -- Introduction -- 1. Population : a dependent variable / Juhani Koponen -- 2. Environment & population growth in Ugogo, Central Tanzania -- pt. 2. Environmental change & economic history in Tanzania's northern highlands -- Introduction -- 3. Environmental control & hunger in the mountains & plains of northeastern Tanzania / Isaria N. Kimambo -- 4. Nature reorganized : ecological history in the plateau forests of the west Usambara Mountains, 1850-1935 / Christopher Conte -- pt. 3. Politics & environmental change -- Introduction -- 5. The precolonial politics of disease control in the lowlands of northeastern Tanzania / James L. Giblin -- 6. 'We don't want terraces' : protest & identity under the Uluguru land usage scheme / Pamela A. Maack -- pt. 4. Environment & mortality -- Introduction -- 7. Environment, community & history : 'nature in the mind' in nineteenth- and early twentieth-century Buha, western Tanzania / Michele Wagner -- 8. Canoe-building under colonialism : forestry & food policies in the inner Kilombero Valley, 1920-40 / Jamie Monson -- 9. Struggles for the land : the political & moral economies of land on Mount Meru / Thomas Spear -- Conclusion/ Isaria N. Kimambo.
Includes bibliographical references (pages 255-265) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Human ecology -- Tanzania -- History; Environmental policy -- Tanzania; Environmental protection -- Tanzania; Tanzania -- Social conditions; Tanzania -- Economic conditions; Tanzania -- Politics and government; Tanzanie -- Conditions sociales; Tanzanie -- Conditions économiques.; Tanzanie -- Politique et gouvernement; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Economic history; Environmental policy; Environmental protection; Human ecology; Politics and government; Social conditions; Tanzania; Milieuverandering; Anthropology; Social Sciences; Anthropogeography & Human Ecology; Écologie humaine -- Tanzanie; Politique de l'environnement -- Tanzanie; Environnement -- Protection -- Tanzanie; Tanzanie -- Politique et gouvernement; Culture -- Related to -- Environment -- History; Tanzania; History